Soybean Performance on Types of Compose and Dosage of Urea Fertilizer in Coastal Lands of Bengkulu - Hesti Pujiwati; Widodo Widodo; Atra Romeida; Dotti Suryati; Muhimmatul Husna; Wahyu Hidayat; Edi Susilo (University of Prof. Dr. Hazairin, SH, 2021)
One of the efforts to increase soybean production in Bengkulu is through the use of coastal land. Coastal land improvement is carried out by adding compost fertilizers. In order to meet the nutrient needs for soybean plants in coastal lands, a combination of compost and urea is needed. This study aims to determine the performance of soybean in the application of various types of compost and doses of urea and determine the type of compost and the best dose of urea in coastal lands. The study was conducted in July-August 2020. The study used a 2-factor and 3-replications in Completely Randomized Block Design, the first factor was the type of compost: P1 = Widelia trilobata; P2 = Tithonia diversivolia; P3 = oil palm empty bunches, P4 = water hyacinth. The second factor is the dose of Urea: N0 = 0 kg.ha-1, N1 = 25 kg.ha-1, N2 = 50 kg.ha-1, N3 = 75 kg.ha-1. The soybean used was the variety of Direng 1. The results showed that the type of compost and the dose of urea were not significantly different in the soybean plant performance variables. The application of 4 types of compost as much as 10 tons ha-1 in coastal lands showed poor growth and yield a little. Thitonia compost gives the highest yields of 0.5 ton.ha-1 and 0.48 ton.ha-1 when giving urea 75 kg.ha-1. Soybean yields are still very low, so it is necessary to double the dose of urea in coastal lands. Keywords: Coastal Land, Direng 1, Compost and Urea.